2018
DOI: 10.24191/jeeir.v6i3.8786
|View full text |Cite
|
Sign up to set email alerts
|

Social influence and eco-label factors towards purchase intention of home products: A PLS approach

Abstract: Consumers today are more aware of environmental issues. This rise in ecologically conscious consumer behavior sometimes known as green consumers has seen an incease in many studies on the nature of green consumers in different markets. This study examines the attitude-behavior relationship that integrates two factors, namely: social influence and knowledge of eco-labels to examine their influence in the intention to purchase green home electronic products.The green home electronic products for this study are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…By testing the direct effects that tourists' general environmental knowledge (H1), tourists' eco-labeling perception (H2), and tourists' pro-environmental behavior (H5) have on purchase intention related to hotels with eco-labels, this study determined that tourists' ecolabeling perception and pro-environmental behavior influence their purchase intention, confirming the results of [21,22,87,92]. However, the direct effect of general environmental knowledge on purchase intention was not determined, contrary to the findings of [23,24,76,77].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…By testing the direct effects that tourists' general environmental knowledge (H1), tourists' eco-labeling perception (H2), and tourists' pro-environmental behavior (H5) have on purchase intention related to hotels with eco-labels, this study determined that tourists' ecolabeling perception and pro-environmental behavior influence their purchase intention, confirming the results of [21,22,87,92]. However, the direct effect of general environmental knowledge on purchase intention was not determined, contrary to the findings of [23,24,76,77].…”
Section: Discussionsupporting
confidence: 63%
“…However, general consumer research mostly supports the link between environmental knowledge and purchase intentions [23,24,77,88]. Research centered on eco-labeling and purchase intentions generally supports this link [21,22,77,87], and these results are also confirmed in tourism studies [86]. Additionally, [86] suggests that eco-labeling could indirectly affect the relationship between general environmental knowledge and purchase intention.…”
Section: Literature Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…their decision is in the form of buying or avoiding buying products in order to be like peers (Akar, Yuksel & Bulut, 2015). Prior researches (Wong, 2019;Akar, Yuksel & Bulut, 2015;Ali, 2018;Hashim, 2018;Ayensa, Mosquera & Murillo, 2016;Lasuin and Ching, 2014;Rompas and Tumewu, 2014) have found that social influence has positive effect on Purchase Intention of consumers. H14: There is a positive relation between Social Influence and Purchase Intention…”
Section: Relationship Between Social Influence and Purchase Intentionmentioning
confidence: 99%
“…To increase purchase intention, SE must be heavily advertised, as most Malaysians are indifferent to new marketing (Noor et al, 2013). Hashim et al (2018) also discovered that young Malaysians' awareness of SE's social impact affected their propensity to purchase. The functional and emotional value of SE items may motivate ethical purchase if it benefits society (Ramayah et al, 2018).…”
Section: Purchase Intention Towards Social Enterprisementioning
confidence: 99%